Causal association between endocrine diseases and lymphoid malignancies explored through two-sample Mendelian randomization analysis - Chenze Zhao; Yu Zhang; Lili Qian; Qing Guo; Ni Zhu (Scientific Reports)
Abstract Endocrine diseases are suspected contributors to lymphoid malignancies, but their precise association is unclear. This study aimed to investigate the causal relationship between various endocrine diseases—specifically type 2 diabetes, obesity, diabetic hypoglycemia, hyperlipidemia, and hyperthyroidism—and lymphoid malignancies, including lymphocytic leukemia and non-Hodgkin’s lymphoma with subtypes like diffuse large B-cell lymphoma and follicular lymphoma. Utilizing data from genome-wide association studies, a two-sample Mendelian randomization analysis was performed. The primary approach involved the inverse-variance weighted method, supplemented by other robust techniques such as the weighted median and MR-Egger regression to ensure reliability. The analysis indicated a significant causal connection between genetically predicted diabetic hypoglycemia and lymphocytic leukemia (Odds ratio = 1.0004, 95% Confidence interval = 1-1.0007, P = 0.03). Conversely, no associations were found for the other endocrine diseases with lymphoid malignancies (P > 0.05 for all). The findings suggest that while diabetic hypoglycemia may influence lymphocytic leukemia risk, further research is necessary to clarify the roles of other endocrine diseases in lymphoid malignancies, including cross-population validations and biological investigations.